(untitled) (Bulletin of criminological association of Ukraine, 2025)
In Ukraine, a significant number of criminal offenses of an environmental nature are registered annually. Based on the research conducted, the author concludes that the average annual rate of registration of criminal offenses under Articles 236-254 of the Criminal Code of Ukraine is 2967 (analysis of statistical data from 2002 to 2024). In addition, a certain part of criminal offenses in the environmental sphere is registered under articles that are not included in Section VIII of the Special Part of the Criminal Code of Ukraine. Pre-trial investigation in such criminal proceedings is carried out by security agencies and units of the State Bureau of Investigation, and this, accordingly, affects the official statistics of registered criminal offenses against the environment. The publication, using the statistical research method, based on the analysis of data on registered criminal offenses against the environment and the study of absolute, average and relative values, analyzes their number, average value, specific weight, crime intensity coefficient, dynamics of the crime level, basic and chain growth rates, absolute growth and trends. The specified information is presented, including in the form of a table and a diagram. Based on a systematic analysis of the array of recorded criminal offenses over the past 23 years, a trend towards a significant increase in the number of criminal offenses against the environment and their specific weight has been proven. Analysis of crime dynamics using basic and chain methods indicates a steady increase in these offenses, which is confirmed by a positive average absolute growth. In addition, the indicator of crime intensity in the field of environmental protection demonstrates a steady growth trend. It has been established that the analyzed type of crime in Ukraine is one of the most complex and poses a threat not only to the environment, but also to the health and well-being of the population. Intensive use of natural resources, insufficient environmental control, corruption in law enforcement and environmental protection agencies, and a low level of environmental awareness of the population contribute to the spread of these criminal offenses. The study of this phenomenon requires criminological analysis, which includes: conducting a systematic study of the indicators and level of environmental crime in Ukraine; studying statistical data used for a systematic, methodical analysis of the state and dynamics of the analyzed crime; establishing the rates of its growth or decline; establishing the percentage ratio of recorded criminal offenses against the environment to the total number of all recorded criminal offenses, etc.